The 1955 green and white yearbook - De La Salle University, Manila (Animo Repository, 1955)
The 1955 Green and White Yearbook was dedicated to fellow alumni who, having left the portals of the Alma Mater, chose to sacrifice the comforts of home and family for a life dedicated to the service of God and humanity.